Measuring Social Conditions and Human Life Expectancy Through Arabic Biographies: A theoretical Framework and an Applied Model for the City of Damascus in the Seventh Century AH - Alrawadieh, Almahdi; Alkhatib, Walid (Jordan Journal for History and Archaeology, 2024)
This research develops an original theoretical framework and scientific methodology for using the books of Arabic biographies for statistical data related to some social conditions, especially average human life expectancy, death rates, causes of death, and the impact of political events. This methodology can be applied for a specific geographical area or a specific political entity, or several regions, or can be expanded to include all countries of the Arab and Islamic world, and in a specific period of time. The data collected can be processed using the Statistical Package for Social Sciences program (SPSS). The study also presents an applied model, based on the theoretical framework, and analysis of the results and testimonies that provide insights based on the collective observed cases. This reveals what is missing from history, and links some of the results to what has been mentioned in the historical sources, which could support or diminish its credibility and reliability. The applied study took as a field of research the city of Damascus at the end of the Ayyubid period and the beginning of the Mamluk period, and was limited to monitoring the average age and some accompanying data.